Simulasi Steady State dan Dynamic pada Kolom De-isobutanizer dengan Penambahan Invers Decoupling pada Sistem Closedloop - Zahrotul Azizah (2477 - 6165, 2021)
Degenerative Control in the Multi Input Multi Output (MIMO) system is an important topic of process control in industry. The interaction between variables in the process becomes a challenge in designing controllers for MIMO systems. Unwanted interactions cause reduced system performance which results in waste. The addition of inverse decoupling is a new strategy in reducing interactions in the process. The proposed strategy was tested on a de-isobutanizer distillation column. The results obtained were that the IAE value in the inverse decoupling added to the 2DoF IMC structure using the Mp-GM tuning method was smaller than the 2DoF IMC structure without inverse decoupling. This structure could reduce the interaction between variables in the MIMO 2×2 process.